Haemodynamic coherence in perioperative setting. Issue 4 (December 2016) - Carsetti, Andrea; Watson, Ximena; Cecconi, Maurizio
Abstract : Over the last decade, there has been an increased interest in the use of goal-directed therapy (GDT) in patients undergoing high-risk surgery, and various haemodynamic monitoring tools have been developed to guide perioperative care. Both the complexity of the patient and surgical procedure need to be considered when deciding whether GDT will be beneficial. Ensuring optimum tissue perfusion is paramount in the perioperative period and relies on the coherence between both macrovascular and microvascular circulations. Although global haemodynamic parameters may be optimised with the use of GDT, microvascular impairment can still persist. This review will provide an overview of both haemodynamic optimisation and microvascular assessment in the perioperative period.